When Gesture “Takes Over”: Speech-Embedded Nonverbal Depictions in Multimodal Interaction - Hsu, Hui-Chieh; Brône, Geert; Feyaerts, Kurt (Frontiers in Psychology, 2021)
The framework of depicting put forward by Clark (2016) offers a schematic vantage point from which to examine iconic language use. Confronting the framework with empirical data, we consider some of its key theoretical notions. Crucially, by reconceptualizing the typology of depictions, we identify an overlooked domain in the literature: “speech-embedded nonverbal depictions,” namely cases where meaning is communicated iconically, nonverbally, and without simultaneously co-occurring speech. In addition to contextualizing the phenomenon in relation to existing research, we demonstrate, with examples from American TV talk shows, how such depictions function in real-life language use, offering a brief sketch of their complexities, arguing also for their theoretical significance.